The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1111/j.1365-2869.2005.00464.x
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic nervous control of the cerebral circulation in sleep

Abstract: Summary Cerebral vessels are extensively innervated by sympathetic nerves arising from superior cervical ganglia, and these nerves might play a protective role during the large arterial pressure surges of active sleep (AS). We studied lambs (n = 10) undergoing spontaneous sleep–wake cycles before and after bilateral removal of the superior cervical ganglia (SCGx, n = 5) or sham ganglionectomy (n = 5). Lambs were instrumented to record cerebral blood flow (CBF, flow probe on the superior sagittal sinus), caroti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 21 publications
1
15
0
1
Order By: Relevance
“…As some anesthetic agents have been shown to suppress autonomic nervous activity (20), tonic SNA may be more pronounced in conscious animals. Supporting this suggestion, SCG ablation increased baseline cerebral blood flow by ϳ1/3 in lambs undergoing spontaneous sleep-wake cycles in the study of Loos et al (27).…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…As some anesthetic agents have been shown to suppress autonomic nervous activity (20), tonic SNA may be more pronounced in conscious animals. Supporting this suggestion, SCG ablation increased baseline cerebral blood flow by ϳ1/3 in lambs undergoing spontaneous sleep-wake cycles in the study of Loos et al (27).…”
Section: Discussionmentioning
confidence: 82%
“…Stimulation of the sympathetic trunk during acute hypertension limits increases in cerebral blood flow (4,6,41). Cervical ganglionectomy has been shown to result in elevated baseline CBF, as well as greater CBF increases associated with natural blood pressure surges (27). Until the present study, no evidence based on direct neural recordings of SNA during potentially damaging elevations in AP was available.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Extraparenchymal and intraparenchymal blood vessels are richly innervated by autonomic nerves (111) and have been shown to modify autoregulation. For example, the lower limit of CBF autoregulation is shifted toward higher blood pressure in parasympathetically denervated rats (128), and a similar shift is observed after stimulation of the cerebral sympathetic system (142).…”
Section: Cerebral Vasoreactivity In the Preterm Brainmentioning
confidence: 99%
“…It has been demonstrated that tonic sympathetic nerve activity constricts the cerebral circulation and restrains baseline CBF in sleep. 12 Cerebral metabolic rate and CBF decrease during stages 3 and 4 NREM sleep, whereas the partial pressure of arterial CO 2 increases because of a reduction in alveolar ventilation. It has been reported that the cerebral circulation during sleep is regulated by metabolic factors depending on the brain activity at a regional level, PO 2 , PCO 2 , pH changes, and autoregulation.…”
Section: Cerebral Hemodynamics During Sleepmentioning
confidence: 99%